2012
DOI: 10.1109/lgrs.2011.2160329
|View full text |Cite
|
Sign up to set email alerts
|

First 3-D Reconstructions of Targets Hidden Beneath Foliage by Means of Polarimetric SAR Tomography

Abstract: This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the exception of pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 16 publications
0
52
0
Order By: Relevance
“…However, it achieves limited vertical resolution and is prone to ambiguities if the number of baselines is low and/or they are irregularly distributed. With better vertical resolution capabilities, Capon beamforming is currently the standard algorithm most widely employed in the tomographic SAR community [28][29][30]. Aiming to achieve finer vertical resolutions, algorithms based on Compressive Sensing (CS) techniques have been proposed to solve the underdetermined system in Equation (6), and have been successfully applied to urban [31,32] and forest scenarios [33].…”
Section: Tomographic Sar Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it achieves limited vertical resolution and is prone to ambiguities if the number of baselines is low and/or they are irregularly distributed. With better vertical resolution capabilities, Capon beamforming is currently the standard algorithm most widely employed in the tomographic SAR community [28][29][30]. Aiming to achieve finer vertical resolutions, algorithms based on Compressive Sensing (CS) techniques have been proposed to solve the underdetermined system in Equation (6), and have been successfully applied to urban [31,32] and forest scenarios [33].…”
Section: Tomographic Sar Imagingmentioning
confidence: 99%
“…where S is a vector with the heights at which at least one peak is found in the unit structure window; R is the length of S; and S represents the mean of vector S. For example, if in a given area the heights in meters of the peaks are [30,25,25,10,10,10,8,2] then S = [30,25,10,8] and R = 4. Finally, the vertical descriptor is normalized by its maximum within the image (or within the set of images that are going to be compared).…”
Section: Forest Structure Estimationmentioning
confidence: 99%
“…The L 2;1 norm not only promotes sparsity along rows and minimizes the energy along columns, but also exponentially reduces the probability of recovery failure in the number of columns ofP. 21 The distribution of the backscattered power over forested areas is not sparse in the object domain 19,[22][23][24] because at least the Fourier spectrum of canopy backscatter is spread along the cross-range direction. Thus, a sparse basis needs to be found.…”
Section: Fully Polarimetric Wavelet-based Distributed Compressive Senmentioning
confidence: 99%
“…Recent published studies demonstrate the great potential of SAR tomography in urban infrastructure monitoring [14][15][16][17][18], vehicle detection and reconstruction [19,20], and forest structure inversion [21,22], etc.. Generally, SAR tomography can be formulated as a 3D reconstruction problem in the wave number domain, or factorized as a 2D conventional SAR processing scheme plus a following 1D parameter estimation stage. The latter strategy is more preferred by researchers due to its superior efficiency, and we will concentrate on it in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], it is reported that the reconstruction of a hidden truck beneath foliage is greatly improved by utilizing multi-polarimetric data. Conventionally, data for different polarimetric channels are processed separately, and then fused together for more information.…”
Section: Introductionmentioning
confidence: 99%